Influence of Pregnancy-Related Conditions on Human Epididymis Protein 4 Serum Levels in Comparison to CA 125 – a Prospective Cohort Trial - Azim, Samira Abdel; Mutz-Dehbalaie, Irene; Wieser, Verena; Berger, Astrid; Böttcher, Bettina; Fiegl, Heidi; Marth, Christian; Widschwendter, Andreas (Geburtshilfe und Frauenheilkunde, 2021)
Introduction HE4 and CA 125, two established biomarkers for assessing adnexal masses in non-pregnant women, are hardly investigated in pregnancy, especially in pregnancy-associated conditions. The aim was to evaluate HE4 and CA 125 levels in the course of pregnancy and to assess the impact of pregnancy disorders, contractions and rupture of membranes on HE4 and CA 125 serum levels in order to use these parameters for evaluation of adnexal masses in pregnancy.Patients and Methods Blood samples (n = 238) of 201 women seen at the Medical University of Innsbruck, Austria, were prospectively obtained during pregnancy and postpartum. Serum concentrations of HE4 and CA 125 were analyzed. ROMA index was calculated by the premenopausal formula.Results HE4 serum levels were highest in the third trimester. Contractions (p < 0.001), rupture of membranes (p = 0.005) and pregnancy-associated diseases (p = 0.003) were associated with higher HE4 levels. As much as 97.5% of HE4 measurements remained below the recommended cut-off for premenopausal women (70 pmol/l). CA 125 levels were not altered by pregnancy-associated conditions. Generally, CA 125 exhibited a wider serum level variability, exceeding the established cut-off of 35 U/ml in 16.4%.Conclusions HE4 serum levels are influenced by several pregnancy-related conditions leading to significantly higher levels in these cases. Despite differing medians according to trimester, the 95th percentile cut-offs and almost all maximum values during the entire course of pregnancy were below the established cut-off for premenopausal women. It was also superior to the performance of ROMA index. Therefore, HE4 can be used as a valuable negative predictive marker for the assessment of adnexal masses during pregnancy.
Keywords: HE4; CA 125; pregnancy; tumor marker; biomarker; adnexal mass